Biomarker-Guided Development of DNA Repair Inhibitors - Cleary, James M; Aguirre, Andrew J; Shapiro, Geoffrey I; D'Andrea, Alan D (Molecular cell, 2020)
Anti-cancer drugs targeting the DNA damage response (DDR) exploit genetic or functional defects in this pathway through synthetic lethal mechanisms. For example, defects in homologous recombination (HR) repair arise in cancer cells through inherited or acquired mutations in BRCA1, BRCA2, or other genes in the Fanconi anemia/BRCA pathway, and these tumors have been shown to be particularly sensitive to inhibitors of the base excision repair (BER) protein poly (ADP-ribose) polymerase (PARP). Recent work has identified additional genomic and functional assays of DNA repair that provide new predictive and pharmacodynamic biomarkers for these targeted therapies. Here, we examine the development of selective agents targeting DNA repair, including PARP inhibitors; inhibitors of the DNA damage kinases ataxia-telangiectasia and Rad3 related (ATR), CHK1, WEE1, and ataxia-telangiectasia mutated (ATM); and inhibitors of classical non-homologous end joining (cNHEJ) and alternative end joining (Alt EJ). We also review the biomarkers that guide the use of these agents and current clinical trials with these therapies.